Perilaku Pemrosesan Informasi melalui Media Sosial dalam Memenuhi Kebutuhan Informasi Mahasiswa - Sari Nilam Putri; Tamrin Kamal; Mulyanti Syas (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study focuses on the use of social media in fulfilling information needs by students of the Da'wah and Communication Sciences Faculty at UIN Imam Bonjol Padang. This study uses Information Seeking theory applied by Wilson. According to Wilson, the information needs as a consequence of a need felt by information users who expect their needs to be fulfilled, then search for information through sources and information services which result in success or failure to find information and choose to use that information or make comparisons information that has been found before. The research method used is quantitative descriptive and questionnaire as a data collection technique. From the results of questionnaires to 93 respondents consisting of 2015, 2016 and 2017 Da'wah and Communication Faculty Students, it was found that the level of information processing behavior through social media in meeting information needs by Da'wah and Communication Sciences students was hight.